2001
DOI: 10.1002/cne.1318
|View full text |Cite
|
Sign up to set email alerts
|

Motoneurons of twitch and nontwitch extraocular muscle fibers in the abducens, trochlear, and oculomotor nuclei of monkeys

Abstract: Eye muscle fibers can be divided into two categories: nontwitch, multiply innervated muscle fibers (MIFs), and twitch, singly innervated muscle fibers (SIFs). We investigated the location of motoneurons supplying SIFs and MIFs in the six extraocular muscles of monkeys. Injections of retrograde tracers into eye muscles were placed either centrally, within the central SIF endplate zone; in an intermediate zone, outside the SIF endplate zone, targeting MIF endplates along the length of muscle fiber; or distally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
193
2
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(229 citation statements)
references
References 46 publications
16
193
2
9
Order By: Relevance
“…However, whether the size principle operates in the ocular motor system remains unclear. Many studies have found the correlation between measures of ocular motoneuron size and recruitment order to be weak or nonexistent (Delgado-Garcia et al 1986;Fuchs et al 1988;Pastor and Gonzalez-Forero 2003;Pastor et al 1991). Yet a relatively strong correlation is observed in the data shown in Fig.…”
Section: Responses To Head Rotationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whether the size principle operates in the ocular motor system remains unclear. Many studies have found the correlation between measures of ocular motoneuron size and recruitment order to be weak or nonexistent (Delgado-Garcia et al 1986;Fuchs et al 1988;Pastor and Gonzalez-Forero 2003;Pastor et al 1991). Yet a relatively strong correlation is observed in the data shown in Fig.…”
Section: Responses To Head Rotationmentioning
confidence: 99%
“…In these studies, synaptic responses were evoked by electrical stimulation of afferent pathways when they were examined at all. As a rule, studies of the VOR employing natural stimulation have been restricted to extracellular recording (Blanks et al 1978;Delgado-Garcia et al 1986;Fuchs et al 1988;Pastor and Gonzalez-Forero 2003;Pastor et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We describe a homogeneous response in recruitment properties of abducens neurons to TeNT applications, whereas on the basis of muscle histochemistry Porter 1981, 1988) and retrograde tracing (Büttner-Ennever et al 2001) at least two types of motoneurons-twitch and nontwitch-could exist. More recently, transneuronal rabies virus tracing, in primates, suggests differences in the afferent inputs to those two likely types of motoneurons (Büttner-Ennever et al 2002).…”
Section: Tent-induced Changes In the Firing Pattern And Discharge Chamentioning
confidence: 99%
“…Disparity between the repair of saccade speed and the persistence of defective ranges of abduction may be due to the selective nature of the nerve fibres damaged or the tempo of their regeneration and remyelination. Large motoneurons within the abducens nucleus innervate singly innervated, twitch muscle fibres, whereas smaller motoneurons around its periphery innervate multiply innervated, non-twitch muscle fibres (Buttner-Ennever et al, 2001. Normal speed but restricted duction might be explained by either predominant damage to nerve fibres from non-twitch nerve fibres motoneurons just outside the abducens nucleus, or by better repair of nerve fibres from twitch motoneurons within the nucleus.…”
Section: Recovery Of Saccadic Velocity In Vith Nerve Palsymentioning
confidence: 99%